A modified fly ash and a method for preparing the same

CN122999651APending Publication Date: 2026-10-30HUANENG JINGTAI THERMAL POWER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611359306.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]针对现有粉煤灰在碳包覆改性过程中,剧烈的处理条件容易导致粉煤灰自身物理结构产生不可逆的破坏的问题

Benefits of technology

[0014]本发明的制备方法,通过三步梯度工艺实现粉煤灰的碳包覆改性。第一步,在低于粉煤灰玻璃相软化温度的第一温度下进行低温预包碳,此时第一碳前驱体发生部分碳化,转化为具有柔韧性和活性官能团的“碳前体”,在粉煤灰表面形成一层连续且具有应力缓冲能力的保护性碳层;第二步,将不同于第一碳前驱体的第二碳前驱体包覆于第一碳层外表面,由于第一碳层表面残留的活性官能团可作为化学锚点,第二碳前驱体可通过化学键合或物理吸附方式牢固附着,形成层间界面;第三步,在高于第一温度的第二温度下进行高温二次碳化,此时第一碳层从部分碳化状态进一步脱氢芳构化,转变为致密碳层,同时第二碳前驱体完全碳化并发生显著体积收缩,两层碳层在界面处相互扩散、化学键合,形成一体化复合碳层。在整个过程中,第一碳层作为热缓冲层和物理屏障,阻隔了高温对粉煤灰的直接冲击,同时其柔韧性吸收并分散了因温度变化和碳层收缩产生的热应力与内应力。本发明在完整保留粉煤灰原始球形形貌、粒径分布及表面孔隙结构的前提下,获得了致密度高、缺陷少、层间结合牢固的复合碳层,克服了现有一步高温碳包覆法性能提升以结构破坏为代价的技术难题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application belongs to the technical field of building materials, and particularly relates to a modified fly ash and a preparation method thereof. The preparation method comprises the following steps: mixing fly ash with a first carbon precursor, performing first heat treatment under a protective atmosphere at a first temperature to form pre-carbonized fly ash loaded with a first carbon layer; mixing the pre-carbonized fly ash with a second carbon precursor different from the first carbon precursor, so that the second carbon precursor is coated on the outer surface of the first carbon layer to obtain twice-coated fly ash; and then performing second heat treatment under a protective atmosphere at a second temperature to obtain modified fly ash; wherein the first temperature is less than the softening temperature of the glass phase in the fly ash; and the second temperature is greater than the first temperature. The present application can effectively protect the physical structure of the fly ash while completing carbon coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of building materials. More specifically, it relates to a modified fly ash and its preparation method. Background Technology

[0002] Fly ash, as a major solid waste from coal-fired power plants, plays a crucial role in its high-value utilization. Carbon coating modification is an effective means to enhance the surface activity of fly ash and expand its application fields (such as adsorbent materials, energy storage materials, and functional fillers). However, existing carbon coating modification technologies have significant drawbacks in application: to achieve a robust carbon layer, high-temperature heat treatment, strong acid / alkali etching, or mechanical grinding are typically required. These harsh treatment conditions can easily cause irreversible damage to the physical structure of fly ash itself. Studies have shown that hollow microspheres in fly ash can break into smaller, irregular particles due to localized overheating during high-temperature reduction reactions, making it difficult to maintain their unique spherical morphology and porous structure. The original spherical morphology, particle size distribution, and surface pore structure of fly ash play a decisive role in its reinforcing effect, dispersion performance, and interfacial bonding ability in composite materials; once damaged, they will severely restrict the application performance of modified fly ash. Therefore, how to achieve uniform carbon coating modification on the surface of fly ash while effectively protecting its original physical structure has become a pressing technical challenge. Summary of the Invention

[0003] To address the problem that harsh processing conditions during the carbon coating modification of fly ash can easily lead to irreversible damage to the physical structure of the fly ash itself, this invention provides a modified fly ash and its preparation method. This invention effectively achieves carbon coating while effectively protecting the physical structure of the fly ash.

[0004] This invention provides a method for preparing modified fly ash, comprising the following steps: S1, Pre-coated carbon: Fly ash is mixed with a first carbon precursor and subjected to a first heat treatment at a first temperature under a protective atmosphere to form pre-carbonized fly ash loaded with a first carbon layer. S2, Secondary Coating: The pre-carbonized fly ash obtained in step S1 is mixed with a second carbon precursor that is different from the first carbon precursor, so that the second carbon precursor coats the outer surface of the first carbon layer to obtain secondary coated fly ash. S3, secondary carbonization: The secondary coated fly ash is subjected to a second heat treatment at a second temperature under a protective atmosphere to obtain modified fly ash. The first temperature is less than the softening temperature of the glass phase in fly ash; The second temperature is greater than the first temperature.

[0005] Preferably, the first carbon precursor and the second carbon precursor are selected from different carbon source materials, and at least one of the following conditions is met: ① the residual carbon rate of the first carbon precursor is higher than that of the second carbon precursor; ② the second carbon precursor contains heteroatoms.

[0006] Preferably, the first carbon precursor is selected from at least one of phenolic resin, asphalt, and polyacrylonitrile; The second carbon precursor is dopamine hydrochloride.

[0007] Preferably, the first temperature is 300~500℃, the second temperature is 600~900℃, and the difference between the second temperature and the first temperature is ≥150℃.

[0008] Preferably, the heating rates in step S1 and step S3 are independently selected from 1 to 10 °C / min, and the heating rate in step S3 is less than the heating rate in step S1.

[0009] Preferably, in step S1, the mass ratio of fly ash to the first carbon precursor is 1:(0.1~1); The mass ratio of fly ash used in step S1 to the second carbon precursor used in step S2 is 1:(0.2~2).

[0010] Preferably, the sphericity of the fly ash is 0.8 to 0.9.

[0011] Preferably, the D50 of the fly ash is 10~20μm.

[0012] Preferably, the particle size distribution of the fly ash satisfies: (D90-D10) / D50≤1.5.

[0013] The present invention also provides a modified fly ash, which is prepared by the preparation method described in the above technical solution.

[0014] The preparation method of this invention achieves carbon coating modification of fly ash through a three-step gradient process. First, low-temperature pre-coating with carbon is performed at a first temperature below the glass phase softening temperature of fly ash. During this process, a first carbon precursor undergoes partial carbonization, transforming into a "carbon precursor" with flexibility and active functional groups, forming a continuous protective carbon layer with stress-buffering capacity on the fly ash surface. Second, a second carbon precursor, different from the first carbon precursor, is coated onto the outer surface of the first carbon layer. Since the residual active functional groups on the surface of the first carbon layer can act as chemical anchors, the second carbon precursor can firmly adhere through chemical bonding or physical adsorption, forming an interlayer interface. Third, high-temperature secondary carbonization is performed at a second temperature above the first temperature. During this process, the first carbon layer further undergoes dehydrogenation and aromatization from a partially carbonized state, transforming into a dense carbon layer. Simultaneously, the second carbon precursor is completely carbonized and undergoes significant volume shrinkage. The two carbon layers diffuse and chemically bond at the interface, forming an integrated composite carbon layer. Throughout the process, the first carbon layer acts as a thermal buffer and physical barrier, blocking the direct impact of high temperatures on fly ash. Simultaneously, its flexibility absorbs and disperses the thermal and internal stresses generated by temperature changes and carbon layer shrinkage. This invention, while fully preserving the original spherical morphology, particle size distribution, and surface pore structure of fly ash, achieves a composite carbon layer with high density, few defects, and strong interlayer bonding, overcoming the technical challenge of existing one-step high-temperature carbon coating methods where performance improvement comes at the cost of structural damage.

[0015] The experimental results show that the present invention achieves uniform carbon coating on the surface of fly ash, and the morphological integrity rate of the modified fly ash obtained reaches more than 88%, and the particle size distribution change rate is less than 4.4%, which effectively protects the original physical structure of fly ash. Detailed Implementation

[0016] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.

[0017] In this article, the technical features described in an open-ended manner include both closed technical solutions composed of the listed features and open technical solutions that include the listed features.

[0018] As used herein, the term "and / or" includes any and all combinations of one or more of the related listed items.

[0019] In this document, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when a range refers to an integer, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.

[0020] In this article, when referring to units for data ranges, if the unit is only followed by the right endpoint, it indicates that the units for the left and right endpoints are the same. For example, 300~500℃ means that the units for the left endpoint "300" and the right endpoint "500" are both in degrees Celsius.

[0021] This invention provides a method for preparing modified fly ash, comprising the following steps: S1, Pre-coated carbon: Fly ash is mixed with a first carbon precursor and subjected to a first heat treatment at a first temperature under a protective atmosphere to form pre-carbonized fly ash loaded with a first carbon layer. S2, Secondary Coating: The pre-carbonized fly ash obtained in step S1 is mixed with a second carbon precursor that is different from the first carbon precursor, so that the second carbon precursor coats the outer surface of the first carbon layer to obtain secondary coated fly ash. S3, secondary carbonization: The secondary coated fly ash is subjected to a second heat treatment at a second temperature under a protective atmosphere to obtain modified fly ash. The first temperature is less than the softening temperature of the glass phase in fly ash; The second temperature is greater than the first temperature.

[0022] Regarding fly ash: In this invention, the sphericity of the fly ash is 0.8~0.9, specifically 0.80, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, and 0.90. Sphericity characterizes the degree to which particles are close to a sphere. The use of the above-mentioned high-sphericity fly ash in this invention has the following advantages: the high-sphericity particles have low frictional resistance during mixing and tumbling, and the carbon precursor solution or slurry can be evenly spread along the spherical surface, avoiding accumulation at the edges; the radii of curvature are similar at all points on the spherical surface, and the thermal stress distribution of the carbon layer is uniform during high-temperature carbonization, with no stress concentration points; the spherical fly ash has good fluidity and high bulk density when used as a filler, which is beneficial for uniform dispersion in composite materials; the carbon layer wrapped on the spherical surface is a continuous spherical shell, and its structural stability is better than that of the carbon layer on the surface of irregular particles.

[0023] In this invention, the D50 of the fly ash is 10~20μm, specifically 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 15.2μm, 16μm, 17μm, 18μm, 18.5μm, 19μm, and 20μm.

[0024] In this invention, the particle size distribution of the fly ash satisfies: (D90-D10) / D50 ≤ 1.5, specifically 1.2 or 1.3. This invention controls the particle size distribution within this narrow distribution system, ensuring that all particles have similar specific surface areas, the adsorption amount of carbon precursors on a unit mass of fly ash tends to be consistent, and the coating thickness is uniform. In a wide distribution system, fine particles (near D10) with larger specific surface areas preferentially adsorb a large amount of carbon precursors, leading to insufficient coating or even exposure of coarse particles (near D90). Furthermore, particles with similar sizes exhibit synchronous thermal expansion and contraction during high-temperature carbonization. If coarse and fine particles are mixed, asynchronous contraction can lead to uneven phenomena such as coarse particles squeezing fine particles and preferential contraction and cracking in the fine particle aggregation area. In some embodiments of this invention, the fly ash specifications are: D50 = 15.2 μm, sphericity 0.85, (D90-D10) / D50 = 1.2. In some embodiments of the present invention, the fly ash has the following specifications: D50 = 18.5 μm, sphericity 0.82, (D90-D10) / D50 = 1.3.

[0025] The fly ash of the specified specifications used in this invention is preferably obtained through pretreatment, i.e., the fly ash is first pretreated to obtain pretreated fly ash, and then subjected to carbon coating treatment. In this invention, the pretreatment process includes: drying, ball milling, and sieving of the fly ash. The drying temperature is preferably 95~105℃, specifically 95℃, 100℃, 105℃, more preferably 105℃; the drying time is preferably 2~4h, specifically 2h, 3h, 4h, more preferably 2h. After the above drying, ball milling is performed; the ball milling speed is preferably 300~400 r / min, specifically 300 r / min, 350 r / min, 400 r / min, more preferably 300 r / min; the ball milling time is preferably 5~15min, specifically 5min, 10min, 15min, more preferably 10min. After the above ball milling, the raw material of the corresponding specifications is sieved out.

[0026] Regarding carbon precursors: In this invention, in step S1, the first carbon precursor is partially carbonized on the surface of fly ash through a first heat treatment, thereby forming pre-carbonized fly ash loaded with a first carbon layer. In this invention, the first carbon precursor and the second carbon precursor are selected from different carbon source materials and at least satisfy one of the following conditions: ① the residual carbon rate of the first carbon precursor is higher than that of the second carbon precursor; ② the second carbon precursor contains heteroatoms. When the residual carbon content of the first carbon precursor is higher than that of the second carbon precursor, the first carbon precursor can form a continuous and complete initial carbon layer even if it is only partially carbonized in the low-temperature pre-coating stage of step S1, ensuring that no fly ash surface is exposed. The second carbon precursor with a lower residual carbon content undergoes significant volume shrinkage in the high-temperature carbonization stage of step S3. The compressive stress generated by this shrinkage makes the second carbon layer more tightly "bind" the first carbon layer and the fly ash core, while also helping to expel gaseous impurities and improve the purity of the carbon layer. When the second carbon precursor contains heteroatoms (the heteroatoms preferably contain N), the heteroatoms are incorporated into the carbon layer lattice during the high-temperature carbonization process, locally destroying the π-conjugated structure and generating structural defects and active sites.

[0027] In this invention, preferably, the first carbon precursor is selected from at least one of phenolic resin, asphalt, and polyacrylonitrile. The second carbon precursor is dopamine hydrochloride.

[0028] In this invention, in step S1, the mass ratio of fly ash to the first carbon precursor is 1:(0.1~1), specifically 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, or 1:1. The mass ratio of fly ash used in step S1 to the second carbon precursor used in step S2 is 1:(0.2~2), specifically 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, or 1:2.0.

[0029] Regarding heat treatment: In this invention, the first temperature is less than the softening temperature of the glassy phase in fly ash, and the second temperature is greater than the first temperature. Preferably, the first temperature is 300~500℃, the second temperature is 600~900℃, and the difference between the second temperature and the first temperature is ≥150℃. Specifically, the first temperature can be 300℃, 350℃, 400℃, 450℃, or 500℃. The second temperature can be 600℃, 650℃, 700℃, 750℃, 800℃, 850℃, or 900℃. The difference between the second temperature and the first temperature is preferably 150~500℃, specifically 150℃, 200℃, 250℃, 300℃, 350℃, 400℃, 450℃, or 500℃. This invention controls the above two temperatures and the difference between them to be ≥150℃, ensuring that the two carbonization steps are in different thermodynamic reaction stages. The first carbon layer obtains sufficient activation energy at the second temperature to undergo structural rearrangement, realizing a gradient evolution path of first forming and then densifying.

[0030] In this invention, the heating rates in step S1 and step S3 are independently selected from 1 to 10 °C / min, and the heating rate in step S3 is less than the heating rate in step S1. Specifically, the heating rate can be 1 °C / min, 2 °C / min, 3 °C / min, 4 °C / min, 5 °C / min, 6 °C / min, 7 °C / min, 8 °C / min, 9 °C / min, or 10 °C / min. Rapid heating leads to a large internal temperature gradient in the sample, with the surface carbonizing and shrinking before the interior expands, generating internal stress. Simultaneously, the rapid release of volatile gases can form pores and cracks in the carbon layer. This invention controls the heating rate more slowly, resulting in a more uniform internal temperature distribution, reduced thermal stress, and slower gas escape, leading to a denser carbon layer structure with fewer defects. Based on this, the present invention also controls the heating rate of the second heat treatment to be lower than that of the first heat treatment: during the first heating, a dense carbon layer has not yet formed on the surface of the fly ash, the gas escape resistance is small, and a relatively fast heating rate can be accepted to improve efficiency; during the second heating, the first carbon layer has become a dense protective layer, the escape path of the residual gas in the fly ash and pores inside becomes longer and the resistance becomes greater, and a slower heating rate can be used to avoid the gas accumulation breaking through the first carbon layer.

[0031] In this invention, the holding time for the first heat treatment is 2-4 hours, specifically 2 hours, 3 hours, or 4 hours. The holding time for the second heat treatment is 3-5 hours, specifically 3 hours, 4 hours, or 5 hours.

[0032] Regarding the protective atmosphere: In this invention, both the first heat treatment in step S1 and the second heat treatment in step S3 are performed under a protective atmosphere. This invention does not have any special restrictions on the type of protective gas used to provide the protective atmosphere; any conventional protective gas is acceptable, such as nitrogen or argon.

[0033] Regarding the operation process for each step: In this invention, preferably, step S1 specifically includes: dispersing fly ash and a first carbon precursor in a solvent, and then evaporating the solvent; subjecting the resulting mixture to a first heat treatment at a first temperature under a protective atmosphere, so that the first carbon precursor partially carbonizes on the surface of the fly ash, forming pre-carbonized fly ash loaded with a first carbon layer. The solvent is preferably anhydrous ethanol. The preferred ratio of fly ash to solvent is 10g:(50~100)mL, specifically 10g:50mL, 10g:60mL, 10g:70mL, 10g:80mL, 10g:90mL, 10g:100mL, and more preferably 10g:50mL. Dispersing the fly ash and the first carbon precursor in the solvent, preferably by stirring and mixing evenly, and then evaporating the solvent.

[0034] In this invention, preferably, step S2 specifically includes: dispersing the pre-carbonized fly ash obtained in step S1 in a medium, adding a second carbon precursor, and stirring the reaction; then, separating the solid and liquid, washing and drying to obtain secondary coated fly ash. The medium is preferably a Tris-HCl buffer solution. In some embodiments of this invention, the pH value of the Tris-HCl buffer solution is 8.5. All the pre-carbonized fly ash obtained in step S1 is added to step S2, and the preferred ratio of fly ash used in step S1 to the medium in step S2 is 10g:(50~100)mL, specifically 10g:50mL, 10g:60mL, 10g:70mL, 10g:80mL, 10g:90mL, or 10g:100mL. The stirring reaction can be carried out at room temperature, such as 25°C. The preferred stirring reaction time is 8~12h, specifically 8h, 9h, 10h, 11h, or 12h, more preferably 12h. After the reaction is complete, solid-liquid separation is performed; the preferred method of solid-liquid separation is filtration. After solid-liquid separation, the obtained solid is washed; the washing is preferably done with water; the water is preferably deionized water. After washing, it is dried. The drying temperature is preferably 60~80℃, specifically 60℃, 65℃, 70℃, 75℃, 80℃, more preferably 60℃. After drying, secondary coated fly ash is obtained.

[0035] The present invention also provides a modified fly ash, which is prepared by the preparation method described in the above technical solution.

[0036] The preparation method of this invention achieves carbon coating modification of fly ash through a three-step gradient process. First, low-temperature pre-coating with carbon is performed at a first temperature below the glass phase softening temperature of fly ash. During this process, a first carbon precursor undergoes partial carbonization, transforming into a "carbon precursor" with flexibility and active functional groups, forming a continuous protective carbon layer with stress-buffering capacity on the fly ash surface. Second, a second carbon precursor, different from the first carbon precursor, is coated onto the outer surface of the first carbon layer. Since the residual active functional groups on the surface of the first carbon layer can act as chemical anchors, the second carbon precursor can firmly adhere through chemical bonding or physical adsorption, forming an interlayer interface. Third, high-temperature secondary carbonization is performed at a second temperature above the first temperature. During this process, the first carbon layer further undergoes dehydrogenation and aromatization from a partially carbonized state, transforming into a dense carbon layer. Simultaneously, the second carbon precursor is completely carbonized and undergoes significant volume shrinkage. The two carbon layers diffuse and chemically bond at the interface, forming an integrated composite carbon layer. Throughout the process, the first carbon layer acts as a thermal buffer and physical barrier, blocking the direct impact of high temperatures on fly ash. Simultaneously, its flexibility absorbs and disperses the thermal and internal stresses generated by temperature changes and carbon layer shrinkage. This invention, while fully preserving the original spherical morphology, particle size distribution, and surface pore structure of fly ash, achieves a composite carbon layer with high density, few defects, and strong interlayer bonding, overcoming the technical challenge of existing one-step high-temperature carbon coating methods where performance improvement comes at the cost of structural damage.

[0037] The experimental results show that the present invention achieves uniform carbon coating on the surface of fly ash, and the morphological integrity rate of the modified fly ash obtained reaches more than 88%, and the particle size distribution change rate is less than 4.4%, which effectively protects the original physical structure of fly ash.

[0038] To further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, and not for limiting the scope of the claims of the present invention.

[0039] Example 1

[0040] Fly ash pretreatment: Fly ash was dried at 105℃ for 2 hours, and then continuously ball-milled for 10 minutes at a ball mill speed of 300 r / min. The raw materials were then sieved to obtain the corresponding specifications. The specifications of the fly ash raw materials obtained after sieving are as follows: fly ash D50 = 15.2 μm, sphericity 0.85, (D90-D10) / D50 = 1.2.

[0041] S1, Pre-coated carbon: 10g of pretreated fly ash and 3g of asphalt were dispersed in 50mL of anhydrous ethanol and stirred until homogeneous. The solvent was evaporated at 80℃. The resulting mixture was placed in a tube furnace and heated to 400℃ at a heating rate of 5℃ / min under N2 atmosphere, held at that temperature for 2h, and then naturally cooled to room temperature to obtain pre-carbonized fly ash loaded with the first carbon layer.

[0042] S2, Secondary Coating: All the pre-carbonized fly ash obtained in step S1 was dispersed in 100 mL of Tris-HCl buffer (pH=8.5), and 5 g of dopamine hydrochloride was added. The mixture was stirred at room temperature for 12 h. After the reaction was completed, the mixture was filtered, washed three times with deionized water, and dried at 60 °C to obtain secondary coated fly ash.

[0043] S3, secondary carbonization: The secondary coated fly ash obtained in step S2 is placed in a tubular furnace and heated to 800°C at a heating rate of 3°C / min under N2 atmosphere. The temperature is held for 3 hours and then naturally cooled to room temperature to obtain the modified fly ash product.

[0044] Example 2

[0045] The difference between this embodiment and Embodiment 1 is that the fly ash raw material obtained after sieving has a D50 of 18.5 μm, a sphericity of 0.82, and (D90-D10) / D50 of 1.3. The rest is the same as in Embodiment 1.

[0046] Example 3

[0047] The difference between this embodiment and embodiment 1 is that the mass ratio of pretreated fly ash to asphalt in step S1 is adjusted to 1:0.8 (the amount of pretreated fly ash is the same as in embodiment 1, and the amount of asphalt is increased to a ratio of 1:0.8), and the rest is the same as in embodiment 1.

[0048] Example 4

[0049] The difference between this embodiment and embodiment 1 is that the mass ratio of pre-carbonized fly ash to dopamine hydrochloride in step S2 is adjusted to 1:1.5 (the amount of pre-carbonized fly ash is the same as in embodiment 1, and the amount of dopamine hydrochloride is increased to a ratio of 1:1.5), and the rest is the same as in embodiment 1.

[0050] Comparative Example 1

[0051] The difference between this comparative example and Example 1 is that a one-step high-temperature method was used without pre-coating carbon. Specifically, 10g of fly ash and 8g of asphalt (corresponding to the total carbon precursor usage in Example 1) were directly mixed, heated to 800°C at 5°C / min under N2 atmosphere, kept at that temperature for 5h, and then naturally cooled to obtain the modified fly ash product.

[0052] Comparative Example 2

[0053] The difference between this comparative example and Example 1 is that dopamine hydrochloride was not coated (i.e. step S2 was not performed), and the rest is the same as Example 1.

[0054] Comparative Example 3

[0055] The difference between this comparative example and Example 1 is that the heat treatment temperature in step S1 is 500°C and the heat treatment temperature in step S3 is 600°C (the difference between the two heat treatment temperatures is <150°C), and the rest is the same as Example 1.

[0056] Product testing: The integrity of the spherical morphology of the modified fly ash product was observed using a scanning electron microscope: the magnification was 5000x, and the integrity of the spheres and whether there were any cracks were observed. The percentage of particles with intact morphology and no cracks in 100 particles was counted. The relevant statistical results are shown in Table 1.

[0057] A laser particle size analyzer was used to verify the change rate of fly ash particle size distribution before and after modification, namely the change rate of (D90-D10) / D50. The relevant test results are shown in Table 1.

[0058] Table 1: Product Test Results

[0059] The test results in the table above show that the modified fly ash obtained by this invention has a morphological integrity rate of over 88% and a particle size distribution change rate of less than 4.4%. This indicates that most particles of this invention have intact morphology without breakage, and the particle size distribution change rate is small after carbon coating modification. This invention effectively protects the physical structure of the fly ash. Compared with the examples, the morphological integrity rate and particle size distribution change rate of Comparative Examples 1-2 are significantly worse, proving that the step-by-step coating and carbonization process of this invention is necessary to effectively protect the physical structure of the fly ash. Compared with the examples, the morphological integrity rate and particle size distribution change rate of Comparative Example 3 are significantly worse, proving that the temperature difference between the two heat treatments must be ≥150℃ to effectively protect the physical structure of the fly ash.

[0060] This document uses specific examples to illustrate the principles and implementation methods of the present invention. The descriptions of these embodiments are merely to aid in understanding the method and core ideas of the present invention, including the best mode, and to enable any person skilled in the art to practice the present invention, including manufacturing and using any device or system, and implementing any combined method. It should be noted that those skilled in the art can make various improvements and modifications to the present invention without departing from its principles, and these improvements and modifications also fall within the scope of protection of the claims. The scope of protection of this patent is defined by the claims and may include other embodiments that can be conceived by those skilled in the art. If these other embodiments have structural elements similar to those expressed in the claims, or if they include equivalent structural elements that are not substantially different from those expressed in the claims, then these other embodiments should also be included within the scope of the claims.

Claims

1. A method for preparing modified fly ash, characterized in that, Includes the following steps: S1, Pre-coated carbon: Fly ash is mixed with a first carbon precursor and subjected to a first heat treatment at a first temperature under a protective atmosphere to form pre-carbonized fly ash loaded with a first carbon layer. S2, Secondary Coating: The pre-carbonized fly ash obtained in step S1 is mixed with a second carbon precursor that is different from the first carbon precursor, so that the second carbon precursor coats the outer surface of the first carbon layer to obtain secondary coated fly ash. S3, secondary carbonization: The secondary coated fly ash is subjected to a second heat treatment at a second temperature under a protective atmosphere to obtain modified fly ash. The first temperature is less than the softening temperature of the glass phase in fly ash; The second temperature is greater than the first temperature.

2. The preparation method according to claim 1, characterized in that, The first carbon precursor and the second carbon precursor are selected from different carbon source materials and at least meet one of the following conditions: ① the residual carbon rate of the first carbon precursor is higher than that of the second carbon precursor; ② the second carbon precursor contains heteroatoms.

3. The preparation method according to claim 1 or 2, characterized in that, The first carbon precursor is selected from at least one of phenolic resin, asphalt, and polyacrylonitrile; The second carbon precursor is dopamine hydrochloride.

4. The preparation method according to claim 1, characterized in that, The first temperature is 300~500℃, the second temperature is 600~900℃, and the difference between the second temperature and the first temperature is ≥150℃.

5. The preparation method according to claim 1, characterized in that, The heating rates in step S1 and step S3 are independently selected from 1 to 10 °C / min, and the heating rate in step S3 is less than the heating rate in step S1.

6. The preparation method according to claim 1, characterized in that, In step S1, the mass ratio of fly ash to the first carbon precursor is 1:(0.1~1); The mass ratio of fly ash used in step S1 to the second carbon precursor used in step S2 is 1:(0.2~2).

7. The preparation method according to claim 1, characterized in that, The sphericity of the fly ash is 0.8~0.

9.

8. The preparation method according to claim 1, characterized in that, The fly ash has a D50 of 10~20μm.

9. The preparation method according to claim 1, characterized in that, The particle size distribution of the fly ash satisfies: (D90-D10) / D50≤1.

5.

10. A modified fly ash, characterized in that, It is prepared by any one of claims 1 to 9.